On Some Recently Discovered Translations from Edgar Allan Poe's Work - by Ștefan Petică – at the End of the 19th Century - Nicoleta Călina (European Scientific Journal, ESJ, 2018)
The first authentic Romanian Symbolist writer - poet, novelist, playwright, journalist, sociologist, Ștefan Petică (1877-1904) - was also a skilled translator, as most of the Romanian writers at the end of the Nineteenth century used to be. For more than 120 years, there was no information on the translator of two volumes rendered into Romanian from Edgar Allan Poe’s work and published in 1896 and, respectively, in 1897, at “Samitca” Publishing House in Craiova.